The effect of pressure on the concentration of methane and carbon dioxide absorption in biogas - Hairul Huda; Revy Aditya; Rivaldo Bodewyn Julian Worotikan; Nurdin Nurdin (Konversi, 2023)
Biogas is playing a vital role in the emerging market for renewable energy. Biogas is an alternative energy that can be used as a substitute for fossil energy. The main composition of biogas is methane gas (CH4) and carbon dioxide gas (CO2) with a small amount of hydrogen sulfide (H2S). Therefore, it is necessary to do treatment to enrich gas methane and reduce CO2 and H2S content in optimizing the use of biogas. Absorption is a CO2 capture technology often used in the chemical industry. A chemical absorption technique using a solvent solution is one of the most widely used techniques to capture CO2. This research uses MDEA (Nmethyldiethanolamine) solvent as an alkanolamine solution dissolved in water. The unit operation usually used to carry out the absorption process is an absorber, and the type of absorber used is a spray column absorber. Simulating variations in pressure on the absorber was conducted in this research. The result of this research is that the increase in pressure will increase the composition percent of CH4 in sweet gas and increase the amount of CO2 absorption in biogas. The best result of absorber pressure is obtained at a pressure of 48 bar. The purity of CH4 and %removal of CO2 in biogas can be solved simply by using the evaluation parameters of the various absorber pressures presented, which we expect to contribute to the biogas industry in the future.